Women's Empowerment in Satriyan Village: Bouquet Making Training as an Effort to Improve the Economy - Bintang Rifqy Algamar; Alifya Nur Faizah; Annisaturrakhillah Firdaus; Anisa Zulfa S.A. Noor; Zulvia Arifatun Nisa; Adeni Adeni (Prosiding Seminar Nasional Manajemen dan Ekonomi, 2024)
Satriyan Village in Tersono District, Batang Regency, still has a low level of women's empowerment. This is due to the low education and skills of women, especially adult women in Satriyan Village, so they spend most of their daily activities at home as housewives. The Religious Moderation Community Service Lecture (KKN) of the State Islamic University of Walisongo Semarang conducts community service by teaching PKK women to make a bouquet in Satriyan Village. This study uses a training method. Those who took part in the training were mothers from the Satriyan Village Family Empowerment and Welfare Driving Team (PKK). The result of this service activity is knowledge about the creative economy, namely making bouquets and having a selling value. In addition, the service participants, namely mothers, have additional expertise.